Laparoscopic Pyelolithotomy for A Staghorn Stone in A Patient with History of Cystectomy and Ileal Conduit - Radfar, Mohammad Hadi; Kashi, Amir Hossein (Urology Journal, 2020)
Laparoscopic pyelolithotomy has recently been introduced for renal stones. However, the use of this technique is limited in patients with history of extensive abdominal surgeries. We present a case of right side staghorn renal stone with history of abdominal open cystectomy who underwent laparoscopic pyelolithotomy with uneventful outcome.